Mesomorphic and fluorescence properties of methyl 4-(4-alkoxystyryl)benzoates. Issue 7 (27th May 2016) - Muhammad, Khushi; Nazir, Saba; Hameed, Shahid; Bechtold, Ivan H.
ABSTRACT: A series of methyl 4-(4-alkoxystyryl)benzoates was synthesised and studied for liquid crystalline and fluorescence properties. The peculiarity of the reaction scheme involved condensation between 4-alkoxybenzaldehyde and 4-(methoxycarbonyl)benzyltriphenyl phosphonium bromide in dichloromethane without any phase separation. The compounds were found thermally stable up to 200°C. The banded or arced focal-conic fan texture of CrE phase was exhibited on cooling the compounds (with chain length > C4 ) below the SmA phase. It was observed that increasing chain length up to C10 enhances mesophase stability. No LC behaviour was manifested by small (up to C3 ) and branched small chain (up to C4 ) members of the series. GRAPHICAL ABSTRACT: